Truman - Mccullough, David (New Delhi: Simon & Schuster, 1992)
The life of Harry S. Truman is one of the greatest of American stories, filled with vivid char- acters-Roosevelt, Churchill, Stalin, Eleanor Roosevelt, Bess Wallace Truman, George Marshall, Joe McCarthy, and Dean Acheson-and dramatic events. In this riveting biography, acclaimed historian David McCullough not only captures the man-a more complex, informed, and determined man than ever before imagined-but also the turbulent times in which he rose, boldly, to meet unprecedented challenges, the last president to serve as a living link between the nineteenth and the twentieth centuries.
Keywords: President; Baiography